Study Performance On Medical Faculty Building of Universitas Muhammadiyah Surakarta With Pushover Analysis - JAENURI, Wahyu Ahmat Hasan, Yenny Nurchasanah,S.T.,M.T, Muhammad Ujianto,S.T.,M.T (2015)
The Medical Faculty Building of Universitas Muhammadiyah Surakarta is a building with six floors of lectures planned able to withstand the maximum earthquake load forces to the earthquake area 3. With the new facility in the world of construction especially in analyzing a structure-based force of quake happens, namely one with pushover analysis. This analysis uses the improved lateral load (increment) gradually until the onset of the plastic hinge and collapsed. This analysis objectives at knowing the capacity curves, peformance point, and formation stages of plastis hinge until the building collapsed structures. Research methods using pushover analysis procedure for A method of spectrum capacity ATC-40. This performance analysis by providing lateral static force with multiplier gradually until a point of reference the structure undergoes a displacement. Planning with partially ductile designing a scheme collapse joint plastis occur in beams first and then followed by the last column. By pro viding a static earthquake force on Y direction by gradually until the building collapsed. The results of the analysis showed that the largest base shear force was 1030,184 tons in the 4th step pushover analysis. Based on the capacity curves obtained peformance point shows base share force V t = 706,779 tons displacement at the 3rd step is 1,2695 m > 0,093 m (D t ). The performance of the structure does not cross the line IO (Immediate Occupancy). Maximum total drift is 0,0041 and a maximum total drift inelastic is 0.003. Thus shows that the building be reviewed is included in levels of Immediate Occupancy (OI). On the third itration, condition of plastis hinges when earthquake force exceeded still to stage a performance of Immediate Occupancy. But the pushover analysis will be impose the structure for suffered a collapse with the indicated first on the 16th step and itration stop at 6th step. The results of the last itration has a very far itration distance when peformance point shows partially ductile concept namely weak beam strong column is not achieved. With shown by the first plastis hinge decreased performance on the column. However the building peformance in the earthquake force plan shows very good and safe results, building in the Immediate Occupancy performance. So if an earthquake with maximum force then the structure will only be having a bit of damage to structures and non-structure and the building can be directly reused.